Perencanaan Upper Structure Proyek Pembangunan Gedung Rektorat Universitas Hasyim Asy’ari menggunakan Metode Sistem rangka pemikul momen khusus.: Perencanaan upper structure (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Hasyim Asy'ari, 2024)
The structure of the rectorate building is planned with reference to earthquake safety planning for buildings and non-buildings, minimum design loads, and structural concrete requirements for buildings. The SRPMK method is used in the analysis of earthquake-resistant building structures. The planned area of ​​the rectorate building has a footprint of 1050 m2 consisting of 5 floors. The calculation stages include load analysis, building structure modeling, and control of inter-floor deviations. The results of the floor deviation analysis meet the requirements, the value of the x-direction floor deviation (Δx) is at most 0.028 mm with a permissible deviation (Δa) of 61.5 mm, the value of the y-direction floor deviation (Δy) is at most 0.107 mm with a permissible deviation (Δa) of 76.9 mm. The column and beam structures use 25MPa concrete quality, 420MPa reinforcement quality. Column dimensions K1 1000/1000mm, K2 800/800mm, K3 600/600mm, beam dimensions B1 500/900mm, B2 500/800mm, B3 400/800mm, B4 350/700mm.